Mengenal Pengadilan Tata Usaha Negara Untuk Mewujudkan Pemerintahan Yang Baik (selayar pandang PTUN): State Administrative Court, Policy, Authority - Melani Safitri; Arif Wibowo (Jurnal Penelitian Multidisiplin, 2023)
The rule of law requires that every action or action taken by public authorities or the government has a clear law or legality based on both written and unwritten laws. The government must be neutral and impartial, before all groups in society, and serve the public interest. But in practice, the terms